Global analysis of the HrpL regulon in the plant pathogen Pseudomonas syringae pv. tomato DC3000 reveals new regulon members with diverse functions. - Hanh N Lam (PLoS ONE, 2014)
The type III secretion system (T3SS) is required for virulence in the gram-negative plant pathogen Pseudomonas syringae pv. tomato DC3000. The alternative sigma factor HrpL directly regulates expression of T3SS genes via a promoter sequence, often designated as the "hrp promoter." Although the HrpL regulon has been extensively investigated in DC3000, it is not known whether additional regulon members remain to be found. To systematically search for HrpL-regulated genes, we used chromatin immunoprecipitation coupled with high-throughput sequencing (ChIP-Seq) and bulk mRNA sequencing (RNA-Seq) to identify HrpL-binding sites and likely hrp promoters. The analysis recovered 73 sites of interest, including 20 sites that represent new hrp promoters. The new promoters lie upstream of a diverse set of genes encoding potential regulators, enzymes and hypothetical proteins. PSPTO_5633 is the only new HrpL regulon member that is potentially an effector and is now designated HopBM1. Deletions in several other new regulon members, including PSPTO_5633, PSPTO_0371, PSPTO_2130, PSPTO_2691, PSPTO_2696, PSPTO_3331, and PSPTO_5240, in either DC3000 or ΔhopQ1-1 backgrounds, do not affect the hypersensitive response or in planta growth of the resulting strains. Many new HrpL regulon members appear to be unrelated to the T3SS, and orthologs for some of these can be identified in numerous non-pathogenic bacteria. With the identification of 20 new hrp promoters, the list of HrpL regulon members is approaching saturation and most likely includes all DC3000 effectors.